Addressing Barriers to Career Development Awards for Early Career Women in Pediatric Psychology. (13th March 2023) - Bates, Carolyn R; Bakula, Dana M; Egbert, Amy H; Gerhardt, Cynthia A; Davis, Ann M; Psihogios, Alexandra M
Abstract: Objective: To provide person and system-level recommendations for supporting early career women in the field of pediatric psychology in writing and submitting National Institutes of Health (NIH) Career Development Award (K award) applications. Recommendations are provided in the context of common barriers, with a focus on practical solutions. Methods: Publicly available NIH reporter data were compiled to examine rates of funding for Society of Pediatric Psychology (SPP) members. Barriers that women face when initiating programs of research are described and applied to the field of pediatric psychology. Results: Of current SPP members, 3.9% ( n = 50) have ever received an NIH K award. Approximately 88.5% of SPP members identify as women, including 89.0% of SPP K award recipients. A table of person- and systems-level recommendations is provided to offer strategies for mentees, mentors/sponsors, institutions, and national organizations to address the barriers discussed. Conclusions: By addressing gender-specific barriers to submitting K award applications, we hope to increase the number of women K awardees and support the scientific advancement of pediatric psychology.